Looking Forward: Cutting-Edge Technologies and Skills for Pathologists in the Future. (December 2019) - Janardhan, Kyathanahalli S.; Kohnken, Rebecca; Turner, Oliver C.; Gurumurthy, Channabasavaiah B.; Kovi, Ramesh C.
Toxicologic pathology is one of the most valuable fields contributing to the advancement of animal and human health. With the ever-changing technological and economic environment, the basic skill set that pathologists are equipped with may require refinement to address the current and future needs. Periodically, pathologists must add relevant, new skills to their toolbox. The Career Development and Outreach Committee of the Society of Toxicologic Pathology (STP) sponsored a career development workshop entitled "Looking Forward: Cutting-edge Technologies and Skills for Pathologists in the Future" in conjunction with the STP 38th Annual Symposium. Experts were chosen to speak on artificial intelligence, clustered regularly interspaced short palindromic repeats technology, microRNAs, and next-generation sequencing. This article provides a summary of the talks presented at the workshop.